Answer:
A. Yes
B. No
C. Yes
D. Yes
E. No
F. Yes
Explanation:
A Write the equation 3n + 4 + 6 = 2n – 14. Yes
B Write the equation 3(n + 4) + 6 = 2(n – 14). No
C Combine like terms. Yes
D Subtract 2n from each side. Yes
E Add 10 to each side. No
F Subtract 10 from each side. Yes
Solution:
sum of 3 times a number and 4 is increased by 6, the result is 2 times a number decreased by 14
Let the number = n
{(3 * n) + 4} + 6 = (2 * n) - 14
3n + 4 + 6 = 2n - 14
3n + 10 = 2n - 14
3n + 10 - 2n = 2n - 14 - 2n
n + 10 = -14
Subtract 10 from each side
n + 10 - 10 = -14 - 10
n = -24